Dithienothiazine Copolymers – Synthesis and Electronic Properties of Novel Redox-Active Fluorescent Polymers - Nau, Jennifer; Müller, Thomas J. J. (Organic Materials, 2021)
Dithienothiazine copolymers are efficiently obtained by Suzuki polymerization or in situ lithiation–Negishi polymerization in good to excellent yields. Gel permeation chromatography was applied to characterize the dispersities and degrees of polymerization of these novel materials. Thermogravimetric analysis shows that the copolymers are stable towards side-chain cleavage up to 200 °C. The materials are deep red to black amorphous solids or resins and their absorption and emission spectra in solution reveal broad absorption bands in the visible and orange to deep red luminescence upon UV excitation. According to the optical band gaps these novel copolymers qualify as a new class of low band gap organic semiconductors.
Keywords: fluorescence; heterocycles; low band gap polymers; Negishi coupling; polymerization; Suzuki coupling